Project based Learning: Sebuah Model Pembelajaran yang Dapat Meningkatkan Hasil Belajar Al-Qur'an Hadis - Saharuddin, Syafitri; Rusmin, Muhammad; Hidayat, Muhammad Yusuf; Jamilah; Majid, Jamaluddin (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to 1) Describe the implementation of the project-based learning model at MAN 1 Majene; 2) Describe the learning outcomes of students in the Al-Qur'an Hadith subject at MAN 1 Majene; 3) Analyse the effect of using a project-based learning model on the learning outcomes of the Al-Qur'an hadith for class XI students at MAN 1 Majene. This type of research is ex post facto quantitative research using simple linear regression analysis. The population in this study was class XI students at MAN 1 Majene, totalling 111 people, while the sample in this study was 34 people. The research instruments used to obtain data were the scale for using the project-based learning model and the learning outcomes scale. This research shows the influence of using a project-based learning model on the learning outcomes of the Al-Qur'an and Hadith of class XI students at MAN 1 Majene.